Normative Distribution of First Metatarsal Axial Rotation. (August 2021) - Steadman, Jesse; Bakshi, Neil; Arena, Christopher; Leake, Richard; Barg, Alexej; Saltzman, Charles L.
Background: First metatarsal (M1) axial rotation is recognized as a clinically relevant component of hallux valgus deformity. Methods to realign the M1 in 3 dimensions have been developed. One goal of these operations is to restore normal rotation of the first ray. The aim of this study is to provide estimates for the normal distribution of M1 rotation in patients without relevant anatomic pathology. Methods: Using stringent clinical and radiographic criteria, we evaluated a set of plain radiograph and weightbearing computed tomography (WBCT) images of 62 feet from a consecutive patient database. Subjects included had normal foot alignment without bunion symptoms. M1 rotation of each foot was measured using 2 unique methods (Saltzman et al and Kim et al methods). Measurement of rotation was performed by 2 observers from coronal WBCT images. Mean values and confidence intervals (CIs) of M1 rotation were calculated for each method. Inter- and intraobserver reliability values were also reported. Results: Mean M1 rotation values of 2.1 degrees (95% CI: 0.9-3.4) and 6.1 degrees (95% CI: 4.4-7.8) were identified using the Saltzman et al and Kim et al methods, respectively. Inter- and intraobserver reliability values were interpreted as excellent for both methods. Conclusion: In this study, we describe the natural distribution of the M1 axial rotation in subjects without bunion or other identifiable bony foot deformities. This information should provide a normative reference for surgeons correcting rotational issues of the first metatarsal. Level of Evidence: Level III, retrospective cohort study.